Layanan Library E-Resources Terhadap Prestasi Belajar Mahasiswa di Perguruan Tinggi Kota Pekanbaru Semester Genap Tahun Akademis 2020/2021 - Thamrin Hasan (Jurnal Gema Pustakawan, 2021)
This study aims to determine the effect of library e-resources services on student learning achievement in the even semester of the 2020/2021 academic year. The method used is a survey with correlational techniques. Research respondents were active students totaling 300 people taken from 20 public and private universities located in Pekanbaru City, using quata sampling technique. The research instrument used a questionnaire, with a Likert scale model. The data analysis technique used is descriptive statistical analysis technique and inferential statistical analysis. The results showed that there was an influence between library e-resources services on student achievement, with a correlation coefficient (R) of 0.029. The value of this correlation coefficient indicates that the level of strength of the relationship is very weak. And obtained the value of the coefficient of determination R Square (R2) of 0.001. This means that it shows that the effect of variable X on Y is only 0.01%. The results of this study are very useful for the improvement and improvement of e-resources library services, especially at universities in Pekanbaru City. The conclusions of this study indicate that student achievement can be improved by providing e-resources library services.